Težnja po novem rekordnem poletu preko 253 m - utopija ali realnost? - Jošt, Bojan (Šport (Ljubljana), 2019)
The ambition to constantly prolong ski flights is everlasting and motivates the spectators at the foot of the ski-flying hill and in front of the television to follow the sport of ski flying. Planica has been the venue of many of the longest ski jumps and flights, first on the old Bloudek ski jump and later on the ski-flying hill designed by the Gorišek brothers. After 2005 the venue of the recordbreaking ski flights became Vikersund, where the ski-flying hill provided better aerodynamic conditions. It is where the Austrian ski jumper Stefan Kraft broke the ski-flying record in 2017 by landing at 253.5 m. Any ski flights to such a distance are extremely dangerous for the athletes. In this year's ski-flying finals in Planica (24 March 2019) the most successful athlete of the season Ryoyu Kobayashi posted the longest jump at 252 m, despite some serious troubles with landing. Further prolongation of ski flights is only possible if the available ski-flying hills are enlarged. The International Ski Federation is bound by this fact professionally and morally. Any ski flight of up to 250 m strongly exceeds its provisions on safe landing on the current HS 225 ski-flying hills that have been enlarged to HS 240 only on paper. The largest ski-flying hills in Vikersund and Planica could be enlarged to HS 250 relatively simply, allowing a maximum ski flight of up to 270 m. This would be a perfect springboard for the construction of a ski-flying hill that would enable athletes to exceed the magic limit of 300 m. Such a ski-flying hill could be built in Planica at the location of the current ski-flying hill, given that the natural terrain is relatively suitable.
Keywords: development; HS 250 ski-flying hill; kinematic analysis; kinematična analiza; letalnica HS 250m; letalnice; razvoj; skakalnice; ski flights; ski jumping; ski-flying hills; smučarski poleti; smučarski skoki